Hubungan Tingkat Pengetahuan dan Tingkat Kepatuhan Minum Obat dengan Tingkat Kekambuhan Lupus Eritematosus Sistemik - Dinda Sinta Rahayu; Ari Udiyono; Lintang Dian Saraswati (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with varied manifestations and characterized by recurring flares. Lack of disease knowledge and non-compliance with drug therapy are an important cause of not achieving treatment targets and worsening lupus symptoms.Methods: This research is a descriptive study with a cross-sectional approach. The research method is quantitative. The sample in this study were 136 patients who came to examine themselves at Central-General Hospital in Semarang City. The sampling technique used in this study was total sampling. This study used a questionnaire to determine the variables studied.Result: The results of this study indicate a significant correlation between the level of knowledge (r=-0,332; p < 0,05) and level of drug adherence (r=-0,644; p < 0,05) to the level of systemic lupus erythematosus flaresConclusion : Based on the results, there is a correlation between knowledge and drug adherence to the level of systemic lupus erythematosus flares. The recommendation given is an integrated approach between patients and health care providers to improve patients understanding of systemic lupus erythematosus flares. Beside of that, specific attention should be paid to integrate the service provision system into the collaborative approach of the patients and his/her family in order to promote the level of drug adherence.